Analisis Unsur Realisme Magis Wendy B.Paris dalam Cerpen “di Tubuh Tarra, dalam Rahim Pohon” Karya Faisal Oddang - Nabilla Defira; Siti Enik Mukhoiyaroh Bambang (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
The phenomenon of myths and traditional beliefs in Indonesian society often serves as a source of inspiration in literary works, particularly through the combination of magical elements and real-life realities. This study aims to describe the forms of magical realism in the short story Di Tubuh Tarra, dalam Rahim Pohon by Faisal Oddang based on Wendy B. Faris’s theory of magical realism. This research employed a qualitative descriptive method with an objective approach. The data source was the short story Di Tubuh Tarra, dalam Rahim Pohon published in Cerpen Pilihan Kompas 2014. Data were collected through reading and note-taking techniques, while the data analysis was conducted by identifying, classifying, and interpreting the data based on Wendy B. Faris’s five characteristics of magical realism, namely irreducible element, phenomenal world, unsettling doubts, merging realms, and disruptions of time, space, and identity. The findings reveal that all five characteristics of magical realism are present in the short story. Magical elements appear through the consciousness of characters after death, the depiction of the Torajan passiliran tradition, and the merging of the human and spiritual worlds. This study shows that magical realism in the short story functions as a representation of the traditions, myths, and belief systems of the Torajan people.